PENGARUH PERSEPSI KEBERMANFAATAN DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP MINAT PENGGUNAAN LAYANAN PEMBAYARAN DIGITAL GO-PAY - Tony Sitinjak, MM (Jurnal Manajemen, 2019)
One of the phenomena that occur in Indonesia in today’s digital economy era is that people began to implement a payment system that use electronic money. Therefore, the researcher sets out the formulation of the problem as follows: "The Effect of Perceived Usefulness and Perceived Ease of Use on the Interest in Using Digital Payment Services Go-Pay." The purpose of this research is toexamine the factors that influence the interest in using electronic money. The model used in this study is the Technology Acceptance Model (TAM). This research was conducted of GO-PAY digital payment service users who are domiciled in Jakarta. The sampling technique used in this study is a convenience sampling technique. While the obtained data is in the form of primary data because the data collection was done by distributing online questionnaires. A total of 125 questionnaire results were received and can be processed by the researcher. The data analysis was carried out by using structural equation modeling (SEM), also known as Partial Least Squares (PLS). The results of the research obtained by researcher show that the perceived usefulness and perceived ease of use has a positive influence on interest in use, and the perceived ease of use has a positive influence on perceived usefulness.